Keeping up with emerging technologies : best practices for information professionals - Hennig, Nicole (Santa Barbara, California : Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2017)
Henning writes for information and library professionals who may be in charge of keeping up with emerging technologies, or who may work where there is no such position and everyone has to do it as part of their job, and for library students interested in technology positions at libraries. Rather than describing specific technologies, she set out methods for keeping up and bringing new technologies into the library's service offerings. Her topics include gathering information: sources and strategies, gathering information: user needs, evaluating information, moving toward implementation, and emerging technologies librarians: defining job roles
Includes bibliographical references (pages 151-167) and index.
oif 16/12/2019
Loans
Keywords: Librarians; Technological literacy; Technological innovations; Information technology; Libraries; Public services (Libraries); Library users